The role of microRNAs in ectopic pregnancy: A concise review - Ghafouri-Fard, Soudeh (Noncoding RNA Res, 2020)
Ectopic pregnancy (EP) is reported in about 1%–2% of pregnant females and is associated with mortality and morbidity. Several genetic and environmental factors might modulate occurrence of EP. Prediction of EP and patients' follow-up is an important task in management of pregnancy. MicroRNAs (miRNAs) as non-coding RNAs with sizes between 21 and 24 nucleotides have been shown to regulate several aspects of implantation and early fetal life. They have potential role in early detection of EP especially considering their presence in body fluids such as serum. Assessment of their expression in serum might provide a noninvasive method for diagnosis and patients' follow-up. However, data regarding their role in EP is not sufficient due to small sample sizes of the studies. Future studies are required to find miRNAs that regulate expression of EP-associated genes such as VEGFA, EGFR, ESR1 and immune response-related genes to provide new diagnostic biomarkers for EP.